The season - MacLean, Sarah (New York : Orchard Books, 2009)
Seventeen-year-old Alexandra must adjust her personality for her mother's expectations of an aristocratic lady--in order for her to attract a suitable husband--but when Alex decides to help the brooding and handsome Gavin solve the mystery behind his father's death, she risks her heart along with her reputation.
Young Adult.
Young Adult
Keywords: Aristocracy (Social class) -- Juvenile fiction; Adventure and adventurers -- Fiction; Aristocracy (Social class) -- Fiction; Historical fiction; Mystery and detective stories; Adventure fiction; Aristocracy -- Fiction; Historical fiction; Mystery fiction; Great Britain -- History -- 1789-1820 -- Juvenile fiction; London (England) -- History -- 1800-1950 -- Juvenile fiction; Great Britain -- History -- 1789-1820 -- Fiction; London (England) -- History -- 1800-1950 -- Fiction; Great Britain -- History -- 1714-1837 -- Fiction; London (England) -- History -- Fiction; Adventure fiction; Mystery fiction